2012
DOI: 10.1051/kmae/2012013
|View full text |Cite
|
Sign up to set email alerts
|

Food preference of the giant mudskipperPeriophthalmodon schlosseri(Teleostei : Gobiidae)

Abstract: Key-words:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 25 publications
2
16
0
4
Order By: Relevance
“…only in the range of 5-7.99 cm with an IRI of 242.4. Zulkifli et al (2012) reported that the most gastric contents of the P. schlosseri are fish and crabs, which are identified as Uca sp., Oryzias sp., and juvenile fish.…”
Section: Periophthalmodon Schlosserimentioning
confidence: 99%
“…only in the range of 5-7.99 cm with an IRI of 242.4. Zulkifli et al (2012) reported that the most gastric contents of the P. schlosseri are fish and crabs, which are identified as Uca sp., Oryzias sp., and juvenile fish.…”
Section: Periophthalmodon Schlosserimentioning
confidence: 99%
“…Một nghiên cứu khác của Zulkifli và nnk. (2012) [12] cũng thực hiện ở Malaysia, cho thấy thức ăn của cá P. schlosseri thường ăn còng (Uca sp. ), cá Sóc (Oryzias sp.…”
Section: đặT Vấn đềunclassified
“…Kết quả này không khác biệt nhiều với nghiên cứu của Zulkifli và nnk. (2012)[12] khi phổ thức ăn của cá P. schlosseri cũng gồm chủ yếu cá Sóc Oryzias sp. và còng Uca sp.…”
unclassified
“…Although both species are highly adaptable to seawater, O. javanicus prefers hyperosmotic conditions while O. dancena favours hypoosmotic conditions at the west coast of Malaysian peninsula where their distribution ranges overlap (15). In addition, O. javanicus is an important component of the mangrove ecosystem (16), and has been used as a valuable marine test fish in several ecotoxicology studies (17, 18).…”
Section: Data Descriptionmentioning
confidence: 99%